Práticas de uso de agrotóxicos no município de Cachoeiras de Macacu, RJ: um estudo de saúde ambiental - Castro, Jane Silva Maia (2009)
In this study, we have surveyed the use of toxic agrochemical products in 40 rural properties in the municipality of Cachoeiras de Macacu, RJ. The survey showed that 22,5% of the farm workers have suffered chemical intoxication. The most common agrochemical products in the region are the insecticide, Decis25CE (highly toxic), and the herbicide, Gramoxone (extremely toxic). We also found that 85% of the farm workers do not use Individual Protection Equipment (IPE). Other preoccupying statistics were: 27,5% of the empty agrochemical containers are simply thrown into the rivers or into the bush; 60% of the farm workers have had no training whatsoever in manipulation of the agrochemical products; and, 85% of those interviewed said that they were able to buy the agrochemical products without an Agronomic Prescription. Slash and burn, application of chemical fertilizers and then plowing in is the agricultural process used throughout the region. It was overwhelmingly obvious that the farmers had no idea that their inadequate agricultural practice impacted seriously on the environment. It was also found that the rural workers of Cachoeiras de Macacu saw no harm in the extensive use of toxic agrochemical products and, in fact, knew of no other way to combat pest infestation. As to the perception of the risks involved in manipulating agrochemicals, we identified three major categories: 70% are aware of the danger, but continue regardless; 27% are unaware of the risks; are, 3%, being aware of risks, have stopped using toxic agrochemicals. Agrochemical products continue intoxicate our farm workers and contaminate our food and the environment. The competent authorities must take energetic steps to reverse this dramatic situation which is decimating those who are the most directly and intensely exposed... our rural workers.